Polarity of peatmoss (Sphagnum) evolution: who says bryophytes have no roots? - Shaw, A. J. (2014)
The class Sphagnopsida (Bryophyta) includes two genera: Ambuchanania and Sphagnum. Ambuchanania contains just one rare species known from two Tasmanian localities, but Sphagnum comprises a speciose clade of mosses that dominates many wetland ecosystems, especially in the boreal zone of the Northern Hemisphere. Recent phylogenetic analyses have resolved well-supported clades within Sphagnum, but polarizing Sphagnum evolution has been problematic because the genus is so isolated that it is difficult to determine homologies between morphological and/or molecular traits within Sphagnum with those of any potential outgroup. DNA sequences from 16 genomic regions representing the mitochondrial, chloroplast, and nuclear genomes (ca. 16 kilobases) were obtained from 24 species of Sphagnum plus one species each from Takakia and Andreaea in order to resolve a rooted phylogeny. Two tropical species, S. sericeum and S. lapazense, were resolved as sister to the rest of the genus and are extremely divergent from all other sphagna. The main Sphagnum lineage consists of two clades; one includes the sections Sphagnum, Rigida, and Cuspidata, and the other includes Subsecunda, Acutifolia, and Squarrosa. The placement of section Subsecunda is weakly supported, but other nodes are strongly supported by maximum parsimony, maximum likelihood, and Bayesian analyses. In addition to homogeneous Bayesian analyses, heterogeneous models were employed to account for different patterns of nucleotide substitution among genomic regions.